Inventory of agroecology related initiatives in Tunisia (1999 – 2023) - Lestrelin, Guillaume; Jaouadi, Rahma (International Center for Agricultural Research in the Dry Areas, 2023)
This working paper presents the results of an inventory of agroecology-related initiatives implemented in Tunisia since 1999. A total of 26 different initiatives were analyzed through a rapid review of grey literature, scientific papers as well as electronic resources found on project/organization websites. The review highlights a fairly significant diversification of the agroecology-related intervention strategies over time – from early initiatives exclusively focused on research-and-development, demonstration and technical support, to sensitization and capacity building approaches after the mid-2000s, and initiatives centered on value chains, multi-stakeholder platforms and credit/financial facilities after the mid-2010s. It also shows that the agroecology principles the most addressed by the different initiatives are ‘co-creation of knowledge’, ‘synergy’, ‘biodiversity’ and ‘soil health’ while the less frequently addressed are ‘animal health’, ‘social values and diets’, ‘fairness’ and ‘connectivity’.